(untitled) (Latakia University Journal -Engineering Sciences Series, 2017)
This paper addresses the subject of design changes management in the context of a multidisciplinary collaborative Building Information Models (BIM) environment. Within Building projects organization field, This research aims to use change management as tool for design and decision making. The proposed method for the management of design changes depends on both modeling the elements of structure based on BIM and using parameter-based design structure matrix as tool for Change Management in a way that will support the effective flow of information between disciplines, and thus reduces design changes, and will be able to trace a series of successive changes within the BIM environment. This paper offers different necessary models to build the DSM; then they are fed by the information of a commercial building project collected from design engineers. The proposed method represents the various dependencies between the parameters of building and evaluates their impact on the levels of elements, the whole system and subsystems in a way that allows to identify the critical parameters and predict some of the iterative cycles of change to avoid unnecessary rework.